CHALLENGING DIAGNOSIS AND MANAGEMENT OF INFECTIOUS SCLERITIS COMPLICATED WITH CORNEAL PERFORATION CAUSED BY MULTI DRUG RESISTANT Proteus mirabilis: Poster Presentation - Case Report - Resident - Pranandito Trunogati; Herwindo Dicky Putranto; Rosy Aldina (Majalah Oftalmologi Indonesia, 2023)
Introduction : Scleritis is a destructive inflammatory disease of sclera and may involve the cornea that associated with an underlying systemic disease and smaller minority are due to infections. The two conditions closely mimic each other, and diagnostic delay can lead to a poor outcome Case Illustration : A 72 year old male presented with severe pain, redness, swelling, and dimness of vision in his left eye. On slitlamp examination, a superonasal scleral nodule with overlying conjunctival defect and corneal ulcer was found. Both ANA test and RA factor were negative. Microbiological investigations of the lessions revealed MDR Proteus mirabilis. His left eye rapidly deteriorated leading to an impending perforation of the sclera and corneal perforation despite intensive antimicrobial therapy, then patient underwent a tibial periosteal graft on his left eye. Although the visual prognosis was poor, structural integrity of the eye was achieved Discussion : Infection is a rare cause of scleritis. Among the organism reported till date, Proteus mirabilis, a gram negative, rod shaped bacterium is the rarest to found. The inciting factors are mostly surgical. There was history of cataract surgery on left eye in this case Conclusion : infectious scleritis is often initially diagnosed as autoimmune, and cause diagnostic delay, the aggressive nature of the associated microbes further complicates the situation. Appropriate diagnosis generally includes lession scrapings with thorough culturing and antibiotic sensitivity testing. Both adequate medical and surgical methods are needed to save the globe from loss